Sustainable healthcare architecture - Guenther, Robin (John Wiley & Sons, Inc., 2013)
"Fully updated with the latest sustainable design information, new project case studies, and performance metrics LEED for Healthcare (new in 20 II) and the online Green Guide for Health Care, the book covers hospitals, ambulatory care, wellness centers, subacute care, and rehabilitation centers"--